Efektivitas Penggunaan Strategi Pembelajaran dalam Meningkatkan Kualitas Pembelajaran di Sekolah Dasar - Sarah Nurul Adha; Hamdi Akbar; Gusmaneli Gusmaneli (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effectiveness of using various learning strategies in improving the quality of learning in elementary schools. Learning strategies are an important component that teachers must prepare to create an effective, interesting learning process that is in accordance with the characteristics and needs of students. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation in several elementary schools. The results of the study indicate that the application of active, cooperative, contextual, and project-based learning strategies can significantly increase student participation, motivation, and learning outcomes. Teachers who are able to choose and adapt learning strategies according to the material and class conditions play an important role in creating a participatory and productive learning environment. In addition, teacher training and the use of discussion and interaction methods have been shown to improve the quality of learning management in the classroom. In conclusion, the effectiveness of learning strategies is greatly influenced by the ability of teachers to design and implement student-centered methods, as well as the support of a conducive learning environment. The implications of this study are expected to be a reference for teachers and schools in choosing and developing appropriate learning strategies to improve the quality of education in elementary schools